European rating of drug harms. (June 2015) - van Amsterdam, Jan; Nutt, David; Phillips, Lawrence; van den Brink, Wim
Background: The present paper describes the results of a rating study performed by a group of European Union (EU) drug experts using the multi-criteria decision analysis model for evaluating drug harms. Methods: Forty drug experts from throughout the EU scored 20 drugs on 16 harm criteria. The expert group also assessed criteria weights that would apply, on average, across the EU. Weighted averages of the scores provided a single, overall weighted harm score (range: 0–100) for each drug. Results: Alcohol, heroin and crack emerged as the most harmful drugs (overall weighted harm score 72, 55 and 50, respectively). The remaining drugs had an overall weighted harm score of 38 or less, making them much less harmful than alcohol. The overall weighted harm scores of the EU experts correlated well with those previously given by the UK panel. Conclusion: The outcome of this study shows that the previous national rankings based on the relative harms of different drugs are endorsed throughout the EU. The results indicates that EU and national drug policy measures should focus on drugs with the highest overall harm, including alcohol and tobacco, whereas drugs such as cannabis and ecstasy should be given lower priority including a lower legal classification.